Adverse effects of long-term corticosteroid use - Xavier de Almeida, Giovanna; Ferreira Silva de Melo, Nathalie; Wiziack Zago, Patricia Maria (InterAmerican Journal of Medicine and Health, 2025)
Corticosteroids, drugs derived from the hormone cortisol, are widely used in clinical practice as part of the treatment for diseases of inflammatory, allergic, immunologic, and oncologic origin. Despite their therapeutic benefits, they should be used with caution, as these drugs are associated with a broad range of adverse effects, some of which are severe and others aesthetically undesirable. Osteoporosis, hyperglycemia, dyslipidemia, infections, cardiovascular diseases, Cushing's syndrome, immunosuppression, and psychiatric disorders are among the most serious adverse effects observed following systemic, prolonged, or high-dose corticosteroid therapy. This descriptive literature review highlights the main adverse effects associated with the use of these medications, presenting current recommendations for their clinical use as well as guidance on how to manage treatment discontinuation when necessary.